OPTIMALISASI DESAIN PROMOSI MELALUI SOSIAL MEDIA DAN MARKETPLACE DALAM PEMASARAN ONLINE UNTUK MENINGKATKAN PENJUALAN PADA UMKM KAMPUNG AKRILIK - Sopali, Mardhatila Fitri; Charli, Chintya Ones; Dewi, Rindy Citra (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2022)
This activity aims to help MSMEs (Micro, Small and Medium Enterprises) in Acrylic Village to be able to maintain their business in the midst of the Covid-19 pandemic, by developing Acrylic Village MSMEs, several wider marketing strategies are used through digital media or e-commerce by using online platforms, media social, google business marketplace and so on. The implementation methodology used in this research is descriptive qualitative with data collection techniques in the form of direct observation, interviews, literature study and documentation. The results of the activities in the research at the Acrylic Village MSMEs, namely the creation of various kinds of e-commerce digital marketing by creating online platforms such as websites, Facebook, Instagram and market places (Sophee, Lazada and Tokopedia), it is hoped that MSMEs can use them as much as possible so that they can expand their sales reach, increasing consumers, increasing sales and making their products known to the wider community and creating more creative content about selling Acrylic Village MSME products on social media and websites.